Cyclic AMP and cell division in Escherichia coli. - D'Ari, R (1988)
We examined several aspects of cell division regulation in Escherichia coli which have been thought to be controlled by cyclic AMP (cAMP) and its receptor protein (CAP). Mutants lacking adenyl cyclase (cya) or CAP (crp) were rod shaped, not spherical, during exponential growth in LB broth or glucose-Casamino Acids medium, and lateral wall elongation was normal; in broth, stationary-phase cells became ovoid. Cell mass was smaller for the mutants than for the wild type, but it remained appropriate for their slower growth rate and thus probably does not reflect early (uncontrolled) septation. The slow growth did not seem to reflect a gross metabolic disorder, since the mutants gave a normal yield on limiting glucose; surprisingly, however, the cya mutant (unlike crp) was unable to grow anaerobically on glucose, suggesting a role for cAMP (but not for CAP) in the expression of some fermentation enzyme. Both cya and crp mutants are known to be resistant to mecillinam, an antibiotic which inhibits penicillin-binding protein 2 (involved in lateral wall elongation) and also affects septation. This resistance does not reflect a lack of PBP2. Furthermore, it was not simply the result of slow growth and small cell mass, since small wild-type cells growing in acetate remained sensitive. The cAMP-CAP complex may regulate the synthesis of some link between PBP2 and the septation apparatus. The ftsZ gene, coding for a cell division protein, was expressed at a higher level in the absence of cAMP, as measured with an ftsZ::lacZ fusion, but the amount of protein per cell, shown by others to be invariable over a 10-fold range of cell mass, was independent of cAMP, suggesting that ftsZ expression is not regulated by the cAMP-CAP complex.